Surgimento do Qualis Artístico: um novo processo de avaliação do produto artístico - Gianetti, Carlos Eduardo (2020)
This work has as general objective to know the postgraduate system in arts in the country, with the purpose of contributing to the improvement of the evaluation process of the Artistic Qualis of the Postgraduate Programs in Arts. Such research is documentary and proposes the analysis and discussion of the instruments used by the Higher Education Personnel Improvement Commission - CAPES, in its Arts area, where there is an indicator called Qualis Artístico created in 2005 for the insertion of such research, artistic products for the evaluation and measurement of postgraduate programs in Arts, as well as for the evaluation of the faculty and students. To this end, the work intends to take a new and controversial Qualis Artístico as an object of research, allowing to understand the specificities of artistic evaluation in Brazil and how such researchers in the area have articulated themselves to assemble the criteria and guidelines. Bourdieu's theoretical perspective, centered on the concepts of field and scientific capital are used to answer such questions. As a principle, research will rescue training and its implications for the organization of the community of art researchers from Brazilian universities.